Debt Management Performance Assessment : Sao Tome and Principe - World Bank (Washington, DC, 2013)
During February 2-14, 2008 a World Bank team comprised of Per-Olof Jonsson and Frederico Gil Sander traveled to Sao Tome e Príncipe to undertake an assessment of the government's debt management capacity and institutions using the Debt Management Performance Assessment Tool (DeMPA). The DeMPA is a methodology for assessing government debt management (DeM) performance through a comprehensive set of indicators spanning the full range of DeM functions. The assessment reveals that despite notable progress since the inception of the debt office in 2004, overall Sao Tome Príncipe meets the minimum requirements set out by the DeMPA only in the fields of evaluation of debt management operations and coordination with monetary policy. The Government does not meet the minimum requirements in the other indicators. The gap between existing practices and the minimum requirements is narrow in some areas. Among the areas for improvement where greater effort is required to reach good practices, the mission identified the legal framework and the managerial structures as key priorities in a reform program.